A 6-month-old girl with mesenteric teratoma: A Case report and literature review - Jin, Yuyan; Zhang, Yanan; Chen, Yongwei; Huang, Jinshi (Frontiers in Pediatrics, 2023)
Mesenteric teratoma is a kind of teratoma originates from the mesentery, which is rare and neglected. We reported this case to emphasize the importance of physical examination in infants. An otherwise healthy 4-month-old girl was presented to the community health service center because her abdomen was distended. Over the next two months, the girl’s abdomen gradually became more dilated. Her examination was notable for abdominal distention with a large mobile nontender abdominal mass. Abdominal ultrasound images and subsequently obtained CT images showed a large, circumscribed cystic and solid mass. It led to the presumptive diagnosis of teratoma of the mesentery. The mass was completely resected during the laparotomy. The pathology, along with the surgical findings and imaging led to the final diagnosis.